Effect of Family-Based Empowerment Model on the Self-Efficacy of Hypertensive Elderly People - Batool Hedayati (University of Social Welfare & Rehabilitation Sciences, 2018)
Objectives Non-communicable diseases are important factors of mortality and morbidity in the elderly people. Among them, hypertension is the most common cardiovascular disease. The family-centered empowerment model is considered to be an important model for promoting health. Thus, the aim of this study was to evaluate the effect of the model on self-efficacy in elderly people with hypertension. Methods & Materials This clinical trial study was conducted on 62 elderly people with hypertension in the Lenjan health center. After sampling by randomized clustering, the subjects were assigned to experimental and control groups. The family-centered empowerment model was used in the experimental group while the control group had one educational class.  The research tools were demographic check list and dimension of self-efficacy of empowerment questionnaire. Post-test was carried out 1 week after the intervention and was followed up after 1.5 months. The obtained data were analyzed by means of SPSS20 Software and Dedicational Statistical Tests, Mann-Whitney, Chi-Square, T-Test, and ANOVAS. Results Before the intervention, both groups were matched with respect to the means of self-efficacy dimension score (P>0.05); but 1 week and 1.5 months after the intervention, significant differences were observed in experimental group (P<0.05).  Conclusion In this study, the family-centered empowerment model showed an effect on the self-efficacy of elderly people with hypertension.